Integrating field-based tests into weekly soccer training sessions: a comparison of physiological demands of three progressive multistage fitness tests and regular training demands - Clemente, Filipe (2022)
Purpose. This study compares the physiological demands of 30-15 Intermittent Fitness Test (30-15IFT), Yo-Yo Intermittent Recovery Test level 1 (YYIRT), and VAMEVAL test as related to training and match demands among youth soccer players. Methods. Overall, 12 under-19 male soccer players (18.21 ± 0.34 years old) were monitored over 3 consecutive weeks for heart rate (HR) responses during training sessions and matches. During this period, they were assessed with 30-15IFT, YYIRT, and VAMEVAL. The measures were taken on the same day of the week to ensure replicable conditions between the tests. Results. The Friedman test revealed significant differences in the average HR (p = 0.006), time in HR zone 3 (p < 0.001), and time in HR zone 4 (p = 0.039) between the tests. Considering the representativeness of the tests in comparison with training sessions and matches, both 30-15IFT and VAMEVAL corresponded to 48% and 46% of the training session load 3 days before the match day (936 ± 447 s) and on the match day (831 ± 533 s), respectively. Conclusions. YYIRT imposed greater time exposure to high HR intensities (in the zones of 80–100% of HR maximum) than VAMEVAL and 30-15IFT. Moreover, the multistage fitness tests corresponded to slightly more than half of the time in which a player was exposed to 80% and 100% of HR maximum during a regular training session and match day. These findings may assist coaches in understanding how to incorporate intermittent fitness tests within training in order to accurately replicate HR responses of match conditions.